2021
DOI: 10.1371/journal.pone.0259862
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in the subthalamic nuclei alters postural alignment and adaptation in Parkinson’s disease

Abstract: Parkinson’s disease (PD) can produce postural abnormalities of the standing body position such as kyphosis. We investigated the effects of PD, deep brain stimulation (DBS) in the subthalamic nucleus (STN), vision and adaptation on body position in a well-defined group of patients with PD in quiet standing and during balance perturbations. Ten patients with PD and 25 young and 17 old control participants were recruited. Body position was measured with 3D motion tracking of the ankle, knee, hip, shoulder and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Switching DBS on increased coupling between segments, including the ankles, which may have simplified the corrective postural responses and consequently have caused the earlier and more pronounced activation of lower leg muscles [ 75 ]. This is supported by several other studies that found that STN-DBS alters postural alignment and consequently can effect postural reflex responses [ 71 , 76 , 105 ]. Studies investigating the latency of electrically induced so-called Hofmann (H) reflex, which is an analogue of the mechanically induced stretch reflex, also provide evidence that STN-DBS may change reflex timing [ 156 , 157 , 158 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Switching DBS on increased coupling between segments, including the ankles, which may have simplified the corrective postural responses and consequently have caused the earlier and more pronounced activation of lower leg muscles [ 75 ]. This is supported by several other studies that found that STN-DBS alters postural alignment and consequently can effect postural reflex responses [ 71 , 76 , 105 ]. Studies investigating the latency of electrically induced so-called Hofmann (H) reflex, which is an analogue of the mechanically induced stretch reflex, also provide evidence that STN-DBS may change reflex timing [ 156 , 157 , 158 ].…”
Section: Discussionsupporting
confidence: 82%
“…Those results might be explained in part by the interference of other early parkinsonian motor symptoms, like rigidity and bradykinesia, which are associated with hypertonic muscle contraction and increased background muscle activity [ 63 , 65 , 102 , 103 , 104 ]. Although there were no obvious signs of significant posture deformities in our patient cohorts, stooped parkinsonian posture with slightly flexed knees and a flexed trunk may have increased background muscle activity as well [ 76 , 91 , 105 , 106 ]. Increased background muscle activity, in turn, increases the co-contraction of agonistic and antagonistic ankle muscles and therefore leads to joint stiffness [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes of such adaptabilities due to, e.g., aging have already been shown for many pro-49 cesses [14], including immune response [15], stem cell development [16], and the locomotor system performance in general [17,18]. As persons with Parkinson's disease (PwPD) show reduced adaptability at different levels (e.g., weaker adaptive responses to balance perturbations during quiet standing [19] or freezing of gait when gait needs to be adapted to external requirements [20]), we hypothesized that PD may specifically lead to reduced RGS.…”
Section: Introductionmentioning
confidence: 99%